E-Digital Transactions From An Islamic Economic Perspective Among Students of The Faculty of Islamic Economics And Business, North Sumatra State Islamic University - Muhammad Zikri Alshaufi; Ahmad Syakir; Nurul Inayah (LP2M IAIN Palopo, 2025)
The phenomenon of game top-up transactions among students is part of the rapidly growing digital economy in the modern era. This study aims to determine the behavior of students at the Faculty of Economics and Islamic Business at UIN North Sumatra in conducting game top-up transactions and to assess their compliance with Islamic economic principles. The method used is a descriptive qualitative approach with data collection through interviews, observations, and documentation of active students who regularly conduct game top-ups. The results of the study show that most students make game top-ups as a form of entertainment and fulfillment of digital recreational needs, but there is still a lack of awareness of sharia principles such as prudence in spending, the prohibition of tabdzir (wastefulness), and the urgency of ensuring that transactions are free from elements of gharar and maisir. This study recommends the importance of strengthening Islamic economic literacy among students so that they can be selective and wise in utilizing digital technology in accordance with sharia values.